On the Evolution of AIDS/HIV Treatment: An Optimal Control Approach - Ali Biswas, Haider (Current HIV Research, 2014)
After more than 30 years of continuous research as well as unselfish efforts, tremendous and exciting developments have been achieved towards the evolution of HIV treatments both in the directions of antiretroviral therapy and effective vaccine for HIV positive patients. Recent research shows that triple-drug antiretroviral therapy can ‘functionally cure’ [1, 2] the HIV positive patients, which is a milestone in the therapeutic treatments of AIDS. Despite the significant progress on the evolution of AIDS/HIV treatments, it is still a curse for the humanity and until today the world’s most serious epidemic as well as leading infectious killer disease. However, Millennium Development Goals (MDGs) Getting to Zero shows a hope to build up a new world without AIDS. In this paper we investigate and focus on those issues of the overall present scenarios of AIDS treatment for the preventive strategies of HIV infections. A mathematical model is analyzed with numerical simulations showing its importance in diseases control and preventions. Optimal control theory is applied to compare the results in the presence of state constraints.
Keywords: mathematical model